2023
DOI: 10.7759/cureus.42214
|View full text |Cite
|
Sign up to set email alerts
|

ChatGPT's Ability to Assess Quality and Readability of Online Medical Information: Evidence From a Cross-Sectional Study

Roei Golan,
Sarah J Ripps,
Raghuram Reddy
et al.

Abstract: Introduction Artificial Intelligence (AI) platforms have gained widespread attention for their distinct ability to generate automated responses to various prompts. However, its role in assessing the quality and readability of a provided text remains unclear. Thus, the purpose of this study is to evaluate the proficiency of the conversational generative pre-trained transformer (ChatGPT) in utilizing the DISCERN tool to evaluate the quality of online content regarding shock wave therapy for erectile d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Researchers also specifically stated that 11.5% of the 104 questions asked to ChatGPT were answered incorrectly. [ 34 ] Golan et al [ 35 ] assessed the quality of online content on shock wave therapy for erectile dysfunction, and found that ChatGPT’s performance in assessing the quality of text content was inadequate and was not consistent with standards set by human evaluators and reliable tools. [ 35 ] Momenaei et al [ 36 ] evaluated the relevance and readability of the medical information provided by ChatGPT-4 regarding common vitreoretinal surgeries for retinal detachments (RDs), macular holes (MHs), and epiretinal membranes (ERMs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers also specifically stated that 11.5% of the 104 questions asked to ChatGPT were answered incorrectly. [ 34 ] Golan et al [ 35 ] assessed the quality of online content on shock wave therapy for erectile dysfunction, and found that ChatGPT’s performance in assessing the quality of text content was inadequate and was not consistent with standards set by human evaluators and reliable tools. [ 35 ] Momenaei et al [ 36 ] evaluated the relevance and readability of the medical information provided by ChatGPT-4 regarding common vitreoretinal surgeries for retinal detachments (RDs), macular holes (MHs), and epiretinal membranes (ERMs).…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] Golan et al [ 35 ] assessed the quality of online content on shock wave therapy for erectile dysfunction, and found that ChatGPT’s performance in assessing the quality of text content was inadequate and was not consistent with standards set by human evaluators and reliable tools. [ 35 ] Momenaei et al [ 36 ] evaluated the relevance and readability of the medical information provided by ChatGPT-4 regarding common vitreoretinal surgeries for retinal detachments (RDs), macular holes (MHs), and epiretinal membranes (ERMs). They noted that the mean Flesch Kincaid Grade Level and Flesch Reading Ease Score were 14.1 ± 2.6 and 32.3 ± 10.8 for RD, 14 ± 1.3 and 34.4 ± 7 for MD, 14.8 ± 1.3 and 28.1 ± 7.5 for ERM.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it demonstrated impressive performance in summarizing conference panels and recommendations [27], generating research questions [28], extracting data from literature abstracts [29], drafting medical papers based on given datasets [30], and generating references from medical articles [31]. ChatGPT was also utilized to evaluate the quality and readability of online medical text regarding shockwave therapy for erectile dysfunction [32]. These applications highlighted the potential of LLMs to condense complex and extensive research materials, allowing for more accessible comprehension and utilization of information in healthcare.…”
Section: Summarizationmentioning
confidence: 99%
“…Accuracy. Several studies highlighted that ChatGPT exhibited inaccuracies when asked to respond to certain questions [14,18,23,29,32,34,35,38,43,50,52,53,64,65,67,71,72]. For instance, ChatGPT could respond with incomplete information or exhibit an inability to distinguish between truth and falsehood [21,69].…”
Section: Reliabilitymentioning
confidence: 99%
“…This was demonstrated when findings related to shockwave therapy for erectile dysfunction diverged from those generated by human experts and trusted tools like DISCERN. 13 AI-based chatbots, including ChatGPT, are programmed and trained using data pertaining to psychiatric conditions. The convenience, ease, and simulation of human-like conversation render these applications as valuable tools for delivering therapy within the realm of psychiatry.…”
Section: Chatgpt In Healthcarementioning
confidence: 99%